THE HERMENEUTIC APPLICATION OF BUDDHADASA BHIKKHU IN STRENGTHENING RELIGIOUS PLURALISM IN CONTEMPORARY THAI SOCIETY FOR PEACEFUL LIVING - (Krajai Raviwanno), Phrakru Pariyatkitchaphirom; Dokbua , Fuen; Anothai, Sawat (Journal of Buddhist Anthropology, 2020)
The objectives of this article were: 1) to study concepts, theories related to hermeneutic science leading to religious pluralism in contemporary society, 2) to study the doctrine’s hermeneutics of Buddhadasa Bhikkhu, 3) to analyze and evaluate the applicative values of doctrine’s hermeneutics of Buddhadasa Bhikkhu in promoting religious pluralism in the present Thai society 4) to create a new body of knowledge and model of promoting religious multi - culture. This research was qualitative research focusing on document study. The presentation was by the analytical description. The results of research were found as follows: The concepts, theories related to hermeneutic science that will lead to religious pluralism in contemporary society. It is a concept that is believed that there are many religions in this world, Is a concept that is believed that in this world, there are many religions, There are different doctrines and practice methods. Everyone must study the doctrine of the religion they respect and other religions to create correct knowledge. The hermeneutic on the doctrine of Buddhadasa Bhikkhu, It is hermeneutic for understanding interfaith so that everyone can reach the heart of their religion and want everyone to withdraw from materialism through the hermeneutic by everyday - dharma language theory. The value of the application of the hermeneutics of Buddhadasa Bhikkhu in promoting religious pluralism in the present Thai society. Creating in terms of promoting a learning society, promoting a peaceful society, strengthening reconciliation society and enhancing a society of awareness. A new body of knowledge and model of religious multi-cultural promotion. Creating a new body of knowledge, such as the model for strengthening religious pluralism "4K1P", means self - knowledge, knowing others, sharing knowledge, methods and peaceful society.